Analisis Kelayakan Investasi Pembelian Mesin Filter Press untuk Pengurangan Limbah Sludge - Muhammad Fidiandri Putra; Ridwan Usman; Rimsa Rusmiland (Universitas Indraprasta PGRI Jakarta, 2017)
PT. Mustika Ratu, Tbk , established since 1981, is anIndonesian manufacturer of cosmetic products and traditional herbal medicines. Total Production in 2016 amounted to 26,330,695 units. In the production process, the company washes the production machine after completion of the process, during which the water as much as 17-34 m3 from the washing is daily discharged to the Wastewater Treatment Plant (WWTP). In a chemical vessel process or water purification process, the normal pH (6 to 9) can be made by adding alum and lime. This lime cleansing process produces a sludge or sludge precipitation. So far, the process of drying sludge still uses method of Drying Bed which dothe drying using sand, coral and fiber. The weakness of this method is it relies solely on the heat of the sun and the drying process takes a longer time during the rainy season. It is therefore necessary to think of purchasing a press filter machine to speed up the drying time and reduce the amount of sludge volume. Sludge waste volume monthly generated is as many as 8 tonon average, with the cost of removal of + Rp. 6,000,000. - if accumulated for 1 (one) year, it becomes Rp. 8,400,000. -. The research methods used are Payback Period Method, Net Present Value and Profitability Index Methods. The results of his research show that with Investment Value of the Purchase of Filter Press Machine of Rp. 170,000,000. - interest of 13% / year, present value of Rp. 93.600.000, a year – the company obtainsa payback period for 22 months (1.83 years), the value of NPV of Rp. 897,593,492. - and the value of Profitability Index (PI) of 6.3. So, it is concluded that the purchase of this machine is feasible.